PKM PELAYANAN FISIOTERAPI DI KLINIK KARYA KOTA PEMATANGSIANTAR - Marolop Parlindungan Napitu; Isa Harpika Br. Ginting; Memo Martua Holong Siregar (Yayasan Nusantara Hasana Berdikari, 2023)
This Community Service Program aims to: Provide Physiotherapy Services, Education and Prevention of Musculoskeletal Disorders, Improve Quality of Life, Develop Student Competencies, and Build Cross-Sector Collaboration. The method used in this Community Service Program is a systematic approach based on the principles of integrated health services. The results of this program are: 1. Effective Physiotherapy Services, 2. Increased Knowledge and Education, 3. High Level of Participant Satisfaction, 4. Developing Student Competencies, 5. Relevance and Effectiveness of the Integrated Approach.